EDUCATIONAL INSTITUTION ACTIVITY IN THE INCLUSIVE EDUCATION PROCESS - Rozenfelde, Marite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article provides a summary of a theoretical study on the main provisions of the activity of the educational institution’s administration in creating and implementing an inclusive educational process at the institution. Inclusive education is teamwork – the responsibility and obligation shared by the whole educational institution is a challenge to the whole team of the educational institution and first of all, a challenge to the administration of the educational institution. Inclusive education can be implemented in various ways all united by organizational culture with positive perception of student diversity, an understanding that the leaders working at educational institutions with their colleagues have a central role in promoting the inclusive culture. The role of administration in the development of the inclusive educational process at an educational institution is to ensure the implementation of the norms concerning the rights of students with special needs to be included, to maintain inclusive policy in the activity of the educational institution, to provide everyone involved in the learning process with information about the special needs of the students, to allocate funds for providing for the special needs, to guarantee accessibility of the educational institution. The administration and the support specialists of the educational institution must work as a team, must develop a plan of measures for the implementation of a further inclusive education process of the educational institution, for providing the support in education where the measures for educational support include determining and assessment of the needs of a student; consultations and support for all students, including the students with special needs, professional development, consultations and support for teachers, the students’ parents and the specialists; consultations of the support team specialists and services, also attracting specialists from other institutions; technical aids and equipment (if necessary); an opportunity to study using sign language and the services of an interpreter (if necessary); transportation services (if necessary, also with an accompanying person); assistant services, etc. The make-up of specialists of the support team of the educational institution – speech and language pathologist, psychologist, social pedagogue, special education pedagogue, medical specialist, etc. can vary depending on the needs and circumstances of the students of the specific educational institution. Work responsibilities of these support team professionals in the general support system of the educational institution are analyzed in the article.